2017
DOI: 10.1002/adfm.201701269
|View full text |Cite
|
Sign up to set email alerts
|

A Materials Roadmap to Functional Neural Interface Design

Abstract: Advancement in neurotechnologies for electrophysiology, neurochemical sensing, neuromodulation, and optogenetics are revolutionizing scientific understanding of the brain while enabling treatments, cures, and preventative measures for a variety of neurological disorders. The grand challenge in neural interface engineering is to seamlessly integrate the interface between neurobiology and engineered technology, to record from and modulate neurons over chronic timescales. However, the biological inflammatory resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
328
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 308 publications
(340 citation statements)
references
References 522 publications
(1,125 reference statements)
3
328
0
Order By: Relevance
“…Soft, nanoscale and bioactive materials have been incorporated into device design to produce electrode arrays with improved biointegration 157 . The broad strategies are to reduce the mechanical mismatch between device materials and brain tissue, reduce the footprint (and invasiveness) of the array, enhance surface porosity to mitigate immune responses, or create a biomimetic or bioactive coating that conceals the implant from the foreign-body response 157 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soft, nanoscale and bioactive materials have been incorporated into device design to produce electrode arrays with improved biointegration 157 . The broad strategies are to reduce the mechanical mismatch between device materials and brain tissue, reduce the footprint (and invasiveness) of the array, enhance surface porosity to mitigate immune responses, or create a biomimetic or bioactive coating that conceals the implant from the foreign-body response 157 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…Polymer blends of silicones and poly(3,4-ethylenedioxythiophene) are the softest reported materials to record extracellular units, with accompanied reductions in microglial attachment 162 . However, these materials introduce challenges for functional device design and minimally damaging deployment 157 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, various studies have demonstrated that electrical stimulation can cause diverse effects such as increases in hippocampal and thalamic volume, increases in blood vessel size and synaptic density, cortical dendrite growth, and changes in mRNA expression—some of which may influence short‐term local somatic and axonal response (Agnew et al, ; Baudry, Oliver, Creager, Wieraszko, & Lynch, ; Brownson, Little, Jarvis, & Salmons, ; Chakravarty et al, ; Cooperrider et al, ; Gall, Murray, & Isackson, ; Hirano, Becker, & Zimmerman, ; Morris, Feasey, ten Bruggencate, Herz, & Hollt, ; Pudenz, Bullara, Dru, & Talalla, ; Sankar et al, ; Veerakumar et al, ; Xia, Buja, Scarpulla, & McMillin, ; Xia et al, ). In chronic neuromodulation or neuroprosthetic applications, additional complexities arise from tissue changes in both the neuronal and non‐neuronal populations due to the implantation injury (glia, neurovasculature, immune cells) (Kolarcik et al, ; Kozai, Jaquins‐Gerstl, Vazquez, Michael, & Cui, ; Michelson et al, ; Salatino, Ludwig, Kozai, & Purcell, ; Wellman & Kozai, ), electrode material degradation (Alba, Du, Catt, Kozai, & Cui, ; Cogan, ; Cogan et al, ; Kozai et al, ; Wellman et al, ; Wilks et al, ), and plastic changes from long‐term electrical stimulation (Agnew et al, ; Baudry et al, ; Brownson et al, ; Chakravarty et al, ; Cooperrider et al, ; Gall et al, ; Hirano et al, ; Merrill et al, ; Morris et al, ; Pudenz et al, ; Sankar et al, ; Veerakumar et al, ; Xia et al, ). Future studies should be aimed at disentangling the complex network of dendrites, axons, and cell bodies of inhibitory and excitatory cells that may be present near the electrode in the brain (Overstreet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of a degenerative foreign body response afflicts both biological tissue as well as the material interface, reducing the long-term recording quality of chronically implanted devices. Consequently, the design of neural interfaces becomes a multi-faceted approach and must take into consideration a wide array of design parameters to functionally integrate electrical materials with biological tissue [7]. Efforts to solve issues of performance reliability and variability by engineering solutions of one aspect of device design prove insufficient when faced with multiple overwhelmingly complex and interconnected modes of failure.…”
Section: Introductionmentioning
confidence: 99%